2018
DOI: 10.1177/1049909118765944
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Home Hospice Transitions of Care in Oncology: Evaluation of Clinical Pharmacists’ Interventions, Hospice Program Satisfaction, and Patient Representation Rates

Abstract: This well-received pilot initiative demonstrated an improvement in local hospice's perception of patient readiness for discharge and a high percentage of accepted pharmacist interventions during discharge medication reconciliation. A larger sample size of patients and longer follow-up period may be needed to demonstrate statistically significant improvements in representation rates postintervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 8 publications
0
23
0
2
Order By: Relevance
“…Studies conducted globally have confirmed the benefit of the integration of the OPT as part the MHT within a variety of settings in improving overall patient care. 2252…”
Section: Contributions To Patient Carementioning
confidence: 99%
“…Studies conducted globally have confirmed the benefit of the integration of the OPT as part the MHT within a variety of settings in improving overall patient care. 2252…”
Section: Contributions To Patient Carementioning
confidence: 99%
“…22 The study designs were varied (case report, descriptive and observational studies, and randomized controlled trial), although three studies did not report their study designs. 17,20,23 The majority of the studies was conducted in ambulatory/clinics (n = 10), 1519,2124,28 followed by inpatient units (n = 2), 25,26 community pharmacy (n = 1), 27 and home care programme (n = 1). 20 The number of patients included in the studies was very variable, ranging from 1 to 215 patients (1 to 162 assessed by pharmacists).…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 shows the activities and-or services provided by clinical pharmacists as well as the duration, frequency and recurrence of pharmacist performance, outcomes measured and method to classify or measure these outcomes, and summary of the results of the studies included in this scoping review. The main activities and-or services provided by pharmacists were the following: conducting medication review (n = 12), 1519,2123,2528 taking medication histories and-or conducting medication reconciliation (n = 6), 1719,21,23,25 educating and counselling patients, caregivers, and families on medication issues (n = 12), 1521,23,24,2628 conducting disease management (focused on pain) (n = 1), 24 and even administrative roles (n = 2), such as medication supply and communication with community resources to ensure that efficient distribution of medication to the patient was not compromised. 19,25 Nine studies clearly described the pharmacist's follow-up with patients (not always with all patients); 1517,1921,24,27,28 among them, five studies clearly reported the time between one assessment and another.…”
Section: Resultsmentioning
confidence: 99%
“…Un pharmacien désirant absolument voir un patient avant son congé devait continuer d'utiliser d'autres approches pour le faire, comme un avis verbal à l'infirmière et au médecin traitant. Plusieurs études mettent en évidence l'utilité d'une liste de contrôle multidisciplinaire à dresser avant le congé d'un patient adulte [13][14][15][16][17][18] . Voirol et collab.…”
Section: Formulaire De Congé Standardiséunclassified